Teaching by doing a professional and personal life - Rascón Moreno, Diego (Alonso de Bonilla, 2016)
Today, when bureaucracy and the university-as-business view prevail in academic evolution, we stop to pay homage to an excellent professional and person who retires, Elizabeth Adams. Some of her colleagues gather here to dedicate a few kind words and their own work to her. This book includes papers on various areas of English Studies such as research methodology, literature (especially poetry), pragmatics, the art of teaching, pronunciation and its transcription, linguistic acquisition, and even painting.